Activist radio and the struggle to empower audiences: a case study of the Zimbabwean history - Chaunza, Garikai (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This study is grounded in my 18-year career in journalism in Zimbabwe. This journey began in January 2006 at the Zimbabwe Broadcasting Corporation (ZBC), where I started as a news reporter. In June 2008, I left ZBC and transitioned to freelance roles, including work at Radio Voice of the People (VOP), which broadcasted from South Africa using Radio Netherlands' transmitters in Madagascar. Simultaneously, I corresponded for The Zimbabwean Newspaper, edited in the UK, printed in Johannesburg, South Africa, and distributed to Zimbabwe, Radio Netherlands, Free Speech Radio News (USA), KPFA Pacifica Foundation Radio (USA), and DW (German). More recently, my work has expanded into the digital domain, contributing to New Zimbabwe, an online newspaper for the Zimbabwean diaspora in the UK, before transitioning to Community Radio Harare. Throughout my 18-year career as a media practitioner and journalist in Zimbabwe, I faced constant state-sanctioned interference, and even physical violence, while executing my responsibilities. Initially, at the Zimbabwe Broadcasting Corporation (ZBC), several colleagues and I, including our news editor, were politically victimised and ultimately fired for covering opposition political players and human rights activists. Later, when I was operating outside state-established media outlets, I experienced a series of threats, intimidation, arrests and detentions by state security. This was also true during my six-year tenure as the chairperson of the Media Institute of Southern Africa's Harare advocacy committee. This experience underscored the importance of studying the history of media activism in this country, focusing on the role that activists have played sustaining the alternative media despite intimidation by the state. I am convinced of the importance documenting their experiences, capturing their contribution to the creation of alternative communication platforms for marginalised audiences. In exploring the literature I discovered that the traditions of activist media, in which I have been involved myself, are rooted in a much older history that can be traced back to pre-independent Zimbabwe. At that time, colonial authorities also restricted media freedoms and employed violence against pro-democracy activities, referred to as nationalists. I decided, for the purpose of this study, to delve into this pre-history of media activism in Zimbabwe, focusing on radio in particular. I wished to gain insight into the way media activists have, over time, sustained their involvement in the traditions of radio practice that can empower marginalised communities. I was conscious that the continued survival of activist radio in this country has often been arduous, with activists facing harassment, arrests, and detentions by authoritarian administrations resisting the opening up of democratic spaces. I wished to trace this history of resistance from its origins in the mid-twentieth century to the time of my own involvement in such radio in the 21st century. In particular, I hoped to identify shared normative foundations as well as shared practices for the implementation of these ideals. Chapter One of the study explores the history of activist radio from the mid-20th century to the present, identifying five distinct phases in Zimbabwe's socio-political history and illustrating how each phase shaped the media landscape. Building on this, Chapter Two establishes a theoretical framework underpinning the values and principles driving media activists to create people-oriented radio projects to empower marginalized communities. Chapter Three delves into the documented history of activist radio within the broader context of media activism in Zimbabwe, engaging with each of the five key moments detailed in Chapter One. Chapter Four outlines the research plan for the empirical fieldwork and discusses its implementation. In Chapter Five, I present interviews with radio activists from the 1970s' nationalist radio and those involved in the pirate radio tradition that re-emerged at the turn of the millennium, sharing their practical experiences. Chapter Six focuses on interviews with community radio advocates, detailing their involvement in radio activism during the first decade of the millennium. Finally, Chapter Seven examines the activities of community radio practitioners, exploring their experiences with unlicensed radio projects and highlighting their creative endeavours.
Keywords: Activism -- Zimbabwe; Radio broadcasting -- Political aspects -- Zimbabwe; Authoritarianism -- Zimbabwe; Democracy -- Zimbabwe; Zimbabwe -- Social conditions; Zimbabwe -- Politics and government